2011
DOI: 10.1097/ta.0b013e31821f7e60
|View full text |Cite
|
Sign up to set email alerts
|

An Orthogeriatric Collaborative Intervention Program for Fragility Fractures: A Retrospective Cohort Study

Abstract: In addition to existing evidence that postoperative orthogeriatric collaboration improves mortality and functional outcomes in older patients with hip fractures, this study suggests that allowing preoperative geriatric input in this model of care can produce even more superior results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 19 publications
3
53
3
2
Order By: Relevance
“…27 A local study reviewed the effectiveness of geri-orthopaedic comanagement and found that in the geri-orthopaedic group, time to surgery was shorter, 1-year mortality rate was lower, and more remained independent in daily living activities. 28 Therefore, geri-orthopaedic care should be implemented in all hospitals in HK to achieve better patient care. This will further improve the KPI for fragility hip fractures in all hospitals in HK.…”
Section: Importance Of Geri-orthopaedic Co-managementmentioning
confidence: 99%
“…27 A local study reviewed the effectiveness of geri-orthopaedic comanagement and found that in the geri-orthopaedic group, time to surgery was shorter, 1-year mortality rate was lower, and more remained independent in daily living activities. 28 Therefore, geri-orthopaedic care should be implemented in all hospitals in HK to achieve better patient care. This will further improve the KPI for fragility hip fractures in all hospitals in HK.…”
Section: Importance Of Geri-orthopaedic Co-managementmentioning
confidence: 99%
“…This includes 'orthogeriatric assessment, rapid optimisation of fitness for surgery, early identification of individual goals for multidisciplinary rehabilitation to recover mobility and independence, and to facilitate return to prefracture residence' [18]. The specific components of most organisational orthogeriatric care pathways do vary, but generally, they include four main steps: pre-operative care, postoperative care, rehabilitation along with secondary prevention Compared to an orthogeriatric liaison model and a joint care model: -Higher inpatient mortality rates [20,46] Compared to an orthogeriatric liaison and joint model of care: -Increased length of stay [47,48] No significant findings reported 2. Orthogeriatric liaison model of care…”
Section: Why Are Fragility Fractures Important?mentioning
confidence: 99%
“…Compared to a usual model of care: -Reduced inpatient mortality rates [46] Compared to a usual model of care: -Reduced length of stay [48] Compared to a usual model of care: -Reduced incidence of delirium in patients [49] -Reduced time to surgery [48] -Improved post-operative patient self-care, mobility and depressive symptoms [50] 3. Post-operative geriatric rehabilitation unit…”
Section: Why Are Fragility Fractures Important?mentioning
confidence: 99%
See 1 more Smart Citation
“…Ja n.a. Suhm et al [22] 2014 [19]. Darüber hinaus ergab eine Studie eine geringere 1-JahresMortalitätsrate bei Patienten in Komanagementbehandlung, allerdings war dies keine allgemeine Feststellung [22,23].…”
Section: Konzept Der Frakturzentrenunclassified